Evaluating the impact of undergraduate ophthalmology education on medical students’ competency in eye care: a cross-sectional study in Jordan - Rami Al-Omari; Khayry Al-Shami; Almu’atasim Khamees; Saja Karaja; Danya Radaideah; Omamah Shlool; Nedalaldeen Alnajadat; Ameera Basim Issa Etoom; Manar Al-Shami (BMC Medical Education)
Abstract Background Ophthalmology is a crucial aspect of primary care, often featuring prominently in both general practice and emergency settings. With over 2 billion individuals worldwide affected by visual impairment, proficiency in basic ophthalmology is essential for general practitioners and emergency physicians. Methods A cross-sectional study was conducted involving 624 medical students from six universities in Jordan. Data were collected using a questionnaire assessing knowledge, diagnostic abilities, and treatment skills in ophthalmology, alongside demographic information and student satisfaction with their ophthalmology rotations. Statistical analyses were performed using SPSS to identify significant associations between variables, with a p-value of less than 0.05 considered statistically significant. Informed consent was obtained from all participants. Results The majority of participants (44.6%) were 23 years old, and 59.8% were female. A significant proportion demonstrated proficiency in basic ophthalmic science, particularly in recognizing refractive problems and anatomical structures of the eye. Gaps were identified in understanding advanced topics such as aqueous regulation and the social-psychological impacts of visual impairment. Diagnostic abilities varied, with most students proficient in diagnosing common conditions like conjunctivitis and cataracts, but less so in identifying complex issues like intraocular foreign bodies. Treatment skills were generally lower, with significant disparities based on university affiliation and cumulative averages. Satisfaction with the ophthalmology rotation was positively correlated with better knowledge and diagnostic abilities. Conclusion The study highlights the variable proficiency in ophthalmic knowledge and skills among medical students, influenced by factors such as university affiliation and satisfaction with ophthalmology rotations.